Relationship between upper body anaerobic power and freestyle swimming performance - Hawley, J. A.; Williams, M. M (International Journal of Sports Medicine, 1991)
The role of upper body anaerobic power in 50 and 400 m swimming performance was assessed in 14 male and 16 female trained swimmers. Peak power, mean power, and a fatigue index were measured. The Wingate Anaerobic Arm Test was used to evaluate capacity for short-term, high-intensity work. Cranking was performed against a constant force, predetermined to yield maximal mechanical power. It was found that: - Peak power was related to 50 m performance (F r = .89; M r = .68); - Mean power was related to 50 m performance (F and M r = .78); - Fatigue index was related to 50 m performance only in females (r = .65); - Mean power was significantly related to distances up to 400 m (100 m r = .78; 200 m r = .60; 400 m r = .63); and - 50 m performance was significantly related to all distances up to 400 m. Upper body anaerobic power is related to sprint swimming. Its importance, although significant, decreases as the racing distance increases. The Wingate Anaerobic Arm Test appears to be an easily administered test of this capacity for swimmers. Implication: The Wingate Anaerobic Arm Test could be added to a testing battery for evaluating effective capacities in swimmers (particularly sprinters or potential swimmers). It may not be as good a measure of specific training effects).